Study on stability analysis of soil nail reinforced slopes under loading based on the discrete element method - Fengling Tan; Guangjing Yin; Pengpeng Zhao; Guocheng Sun; Zhe Li; Zongtang Zhang (PLoS ONE, 2026)
Soil nailing is widely used to improve slope stability, yet the mechanical response of soil-nailed slopes subjected to surcharge loading remains insufficiently understood, particularly at the mesoscopic level. In this study, the discrete element method (DEM) was employed to investigate the progressive failure process, macroscopic stability, and micromechanical behaviors of a soil-nailed slope subjected to point loading and distributed linear loading with varying magnitudes and loading widths. The numerical results show that surcharge loading significantly reduces slope stability and increases deformation. Under point loading, the safety factor decreases continuously with increasing load magnitude and the deformation remains highly localized. Under linear loading, the safety factor decreases sharply as the loading width increases from 0 to approximately 1.5–2.0 m, and then tends to stabilize, whereas displacement continues to increase monotonically. Micromechanical analyses indicate that surcharge loading promotes rapid accumulation of elastic strain energy, intensifies particle rotation, and increases stress heterogeneity within the slope. Load distribution also strongly affects the force transfer mechanism in the reinforcement system: narrow loads are mainly resisted by upper nails, while wide distributed loads mobilize deeper nails and shift the stabilizing effect to lower reinforcement layers. The results suggest that surcharge loads near the slope crest should be carefully controlled, and that sufficient setback distance is important for limiting stress transmission into the active failure zone. These findings provide insight into the failure mechanism of soil-nailed slopes under surcharge loading and offer practical guidance for reinforcement design.